Evaluation of Medicinal Values of Gymnopetalum chinense (Lour.) Merr., a Lesser Known Cucurbit from Eastern Ghats of India - Sanjeet Kumar; Gitishree Das; Han-Seung Shin; Pradeep Kumar; Jayanta Kumar Patra (Brazilian Archives of Biology and Technology, 2017)
ABSTRACT >The in vitro antimicrobial activity of Gymnopetulum chinense (Cucurbitaceae), a lesser known climber of Eastern Ghats and recently recorded species from Odisha, India was studied against five selected human pathogenic bacteria (Streptococcus mutans, S. pyogenes, Vibrio cholerae, Shigella flexneri and Salmonella typhi), by agar well diffusion (AWD), disc diffusion (DD) and broth dilution methods. Different solvent extracts were prepared from the leaves of G. chinense using various solvents viz. n-hexane, chloroform, methanol, acetone and aqueous. The nomenclature, detailed description and photographs of the plant are provided to facilitate its easy identification. The leaf extract showed presence of phenolic compounds, tannin, saponin, flavonoids and glycosides. It was examined that methanol extract showed highest zone of inhibition (16.66 mm) against S. pyogenes using DD assay. Similar results were examined as lowest MIC values were found with methanol leaf extract against S. pyogenes and S. mutans (200 µg/ml). Present study showed first report of this plant as natural antibacterial agents and highlights the importance of G. chinense in curing the bacterial infections.